A common classification framework for histone sequence alterations in tumours: an expert consensus proposal. Issue 2 (7th May 2021) - Leske, Henning; Dalgleish, Raymond; Lazar, Alexander J; Reifenberger, Guido; Cree, Ian A
Abstract: The description of genetic alterations in tumours is of increasing importance. In human genetics, and in pathology reports, sequence alterations are given using the human genome variation society (HGVS) guidelines for the description of such variants. However, there is less adherence to these guidelines for sequence variations in histone genes. Due to early cleavage of the N‐terminal methionine in most histones, the description of histone sequence alterations follows their own nomenclature and differs from the HGVS‐compliant numbering by omitting this first amino acid. Next generation sequencing reports, however, follow the HGVS guidelines and as a result, an unambiguous description of sequence variants in histones cannot be provided. The coexistence of these two nomenclatures leads to confusions for pathologists, oncologists, and researchers. This review provides an overview of tumour entities with sequence alterations of the H3‐3A gene (HGNC ID = HGNC:4764), highlights the problems associated with the coexistence of these two nomenclatures, and proposes a standard for the reporting of histone sequence variants that allows an unambiguous description of these variants according to HGVS principles. We hope that scientific journals will adopt the new notation, and that both geneticists and pathologists will include it in their reports. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.